Polymer coated graphite negative electrode material as well as preparation method and application thereof

By using cyclized polyacrylonitrile to coat graphite negative electrode materials, the problem of insufficient electrolyte compatibility and mechanical stability in lithium-ion batteries is solved, efficient rate and cycling performance improvements are achieved, and production costs are reduced and energy consumption, meets green and environmental protection requirements.

CN119133379APending Publication Date: 2024-12-13STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3

Patent Information

Application Number
CN202411023079.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have problems such as poor electrolyte compatibility and insufficient mechanical stability in lithium-ion batteries, resulting in irreversible capacity loss and degradation of cycling performance. In addition, the traditional pyrolysis carbon coating process has high temperature demand, high energy consumption and toxic substances. Emissions and environmental issues.

Method used

The polyacrylonitrile coated graphite negative electrode material is prepared by ball milling method and liquid phase coating method, and the cyclized polyacrylonitrile coated graphite negative electrode material is obtained by low-temperature heat treatment to enhance machinery and chemical stability, reduce toxic substance emissions and reduce energy consumption.

Benefits of technology

It effectively improves the rate performance and circulation performance of graphite negative electrode, avoids the crushing and falling off of the cladding material, reduces production costs, and achieves green and environmentally friendly industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133379A_ABST
    Figure CN119133379A_ABST
Patent Text Reader

Abstract

The invention relates to a polymer coated graphite negative electrode material and a preparation method and application thereof, the preparation method comprises the following steps: mixing polyacrylonitrile and graphite by adopting a ball milling method, then treating by adopting a liquid phase coating method to coat the surface of the graphite with a layer of polyacrylonitrile, and then carrying out low-temperature heat treatment to obtain the cyclized polyacrylonitrile coated graphite negative electrode material. The compact, flexible, high-electron and high-ion conductive coating is constructed on the surface of the graphite, so that the mechanical stability and the chemical stability of the graphite negative electrode material are effectively enhanced, the problem that a coating material is easy to break and fall off in a long-cycle process in the prior art is avoided, the interface performance of a graphite negative electrode and an electrolyte is improved, and the service life of the graphite negative electrode is prolonged. The volume expansion of the graphite negative electrode material is inhibited, the electrochemical activity of the graphite negative electrode material is enhanced, the electron transmission rate is accelerated, the rate capability and the cycle performance of the graphite negative electrode are further improved, and the preparation process is simple, green and environment-friendly, and is beneficial to industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a polymer-coated graphite negative electrode material and a preparation method and application thereof. Background Art

[0002] The large-scale commercial use of lithium-ion batteries is inseparable from the development of graphite negative electrode materials, whose important performance parameters include charging speed, cycle life, first coulombic efficiency and energy density. However, untreated graphite materials have many defects, which are mainly reflected in two aspects. On the one hand, its electrolyte compatibility is poor. The solvent molecules in the electrolyte will react with lithium ions during the first charge and discharge process to form SEI film, resulting in irreversible capacity loss and low first coulombic efficiency. On the other hand, the interlayer binding force of graphite is a weak van der Waals force. After lithium ion deintercalation, the co-embedding of solvent molecules will cause the peeling and crushing of the graphite layer structure. In addition, with the charge and discharge cycle, the rupture and generation of the SEI film will also be repeated, the SEI film will gradually thicken, and its electronic conduction effect will gradually weaken, thereby increasing the loss of irreversible capacity of the graphite electrode, resulting in damage to the rate performance and cycle performance of the graphite electrode. Therefore, the graphite must be modified to improve the rate performance and cycle stability of the graphite negative electrode.

[0003] Surface coating is currently the main method to improve the performance of graphite negative electrode materials. Its main function is to coat the active sites on the graphite surface, reduce the occurrence of irreversible side reactions, reduce the specific surface area of ​​natural graphite, inhibit the formation of SEI film, and improve Li + The diffusion rate in the solid phase promotes the solvation of Li + Desolvation reduces adverse reactions such as lithium precipitation. At the same time, it isolates the graphite particles from the electrolyte to prevent the co-embedding of solvent molecules, which leads to a decrease in capacity. It also restricts and buffers the volume expansion of graphite, increasing the stability of the cycle.

[0004] At present, the most common graphite surface coating materials include amorphous carbon. For example, CN103682350A discloses a method for preparing a lithium battery negative electrode material of asphalt liquid-phase coated modified artificial graphite, which dissolves artificial graphite and asphalt in a dispersant to obtain a mixed solution, spray-dries the mixed solution to obtain a composite powder, and directly carbonizes to obtain an asphalt liquid-phase coated modified artificial graphite material. CN103647055A discloses a negative electrode material of epoxy resin modified graphite and a preparation method thereof, which obtains a negative electrode material of epoxy resin modified graphite by grinding, high-temperature curing, carbonizing and crushing an organosilicon-modified epoxy resin and natural graphite. Compared with uncoated graphite, the graphite negative electrode coated with pyrolytic carbon has a significant improvement in reversible capacity, cycle performance, and low-temperature rate performance. However, in the existing pyrolytic carbon coating process, high-temperature pyrolysis or high-temperature curing is prone to particle bonding and uneven coating, and the coating material may break and fall off, which limits the cycle performance and rate performance of the graphite negative electrode, making it difficult to meet the current performance requirements of the lithium-ion battery industry for graphite negative electrodes. Importantly, the coating process also uses a large amount of toxic organic solvents, which increases the emission of toxic substances, has high production costs, is not environmentally friendly, and is harmful to health. In addition, the carbonization process requires high temperatures and high energy consumption, which does not conform to the concept of energy conservation, emission reduction, and green development.

[0005] In summary, how to provide a graphite surface carbon coating method that can enhance the mechanical stability and chemical stability of graphite negative electrode materials, thereby improving the rate performance and cycle performance of the graphite negative electrode, while being green, environmentally friendly and low in energy consumption, has become a problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the present disclosure provides a polymer-coated graphite negative electrode material and a preparation method and application thereof. The polymer-coated graphite negative electrode material uses cyclized polyacrylonitrile as the coating layer of graphite, which effectively enhances the mechanical stability and chemical stability of the graphite negative electrode, thereby improving the rate performance and cycle performance of the graphite negative electrode. At the same time, the preparation method can not only reduce the emission of toxic substances, but also reduce energy consumption, significantly reduce production costs, improve environmental protection performance, and achieve green production.

[0007] In a first aspect, the present disclosure provides a polymer-coated graphite negative electrode material, wherein the polymer includes cyclized polyacrylonitrile.

[0008] In the present disclosure, the cyclized polyacrylonitrile not only has high electronic conductivity and strong lithium ion conductivity, but also has excellent mechanical stability. The use of the cyclized polyacrylonitrile to construct a dense, flexible, high electronic and high ion conductive coating on the surface of the graphite negative electrode material can effectively enhance the mechanical stability and chemical stability of the graphite negative electrode material, 1) avoiding the problem of easy breakage and shedding of the coating material in the prior art during long cycles; 2) improving the interface performance between the graphite negative electrode and the electrolyte, inhibiting the interface reaction and the decomposition of the electrolyte; 3) inhibiting the volume expansion of the graphite negative electrode material; 4) at the same time, the nitrogen element contained in the cyclized polyacrylonitrile realizes the doping modification of the graphite, enhances its electrochemical activity, accelerates the rate of electron transfer, and thus improves the rate performance and cycle performance of the graphite negative electrode.

[0009] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.

[0010] As a preferred technical solution of the present disclosure, the coating thickness of the polymer is 35-45 nm, such as 35 nm, 37 nm, 40 nm, 42 nm or 45 nm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0011] Preferably, the particle size of the graphite is 8-15 μm, such as 8 μm, 10 μm, 12 μm or 15 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0012] In a second aspect, the present disclosure provides a method for preparing the polymer-coated graphite negative electrode material as described in the first aspect, the preparation method comprising:

[0013] (1) ball-milling polyacrylonitrile and graphite to obtain a mixed powder;

[0014] (2) treating the mixed powder obtained in step (1) by a liquid phase coating method so that the surface of the graphite is coated with a layer of polyacrylonitrile to obtain a polyacrylonitrile-coated graphite negative electrode material;

[0015] (3) heat-treating the polyacrylonitrile-coated graphite negative electrode material obtained in step (2) to obtain a cyclized polyacrylonitrile-coated graphite negative electrode material.

[0016] The present invention discloses a method of coating polyacrylonitrile on the surface of graphite by ball milling and liquid phase coating to obtain polyacrylonitrile-coated graphite negative electrode material (G@PAN); the obtained polyacrylonitrile-coated graphite negative electrode material can be further subjected to heat treatment to obtain cyclized polyacrylonitrile-coated graphite negative electrode material (G@C-PAN). The preparation method is green and environmentally friendly, has low pollution and low energy consumption, and is conducive to industrial production.

[0017] As a preferred technical solution of the present invention, the added mass of polyacrylonitrile in step (1) is 10-20% of the added mass of graphite, for example, 10%, 12%, 14%, 16%, 18% or 20%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0018] In the present disclosure, controlling the appropriate ratio of polyacrylonitrile to graphite helps to improve the mechanical stability and chemical stability of the graphite negative electrode material. If the amount of polyacrylonitrile added is too much, the particle volume of the graphite composite negative electrode material will increase, the irreversible capacity will increase, and at the same time, the lithium ion deintercalation and formation will increase to a certain extent, and the lithium ion conductivity will decrease; if the amount of polyacrylonitrile added is too little, the coating protection effect cannot be fully exerted, causing part of the uncoated graphite surface to contact the electrolyte, thereby affecting the electrochemical properties such as cycle stability and rate.

[0019] As a preferred technical solution of the present invention, the ball-to-material ratio of the ball milling mixing in step (1) is (8-12):1, for example 8:1, 9:1, 10:1, 11:1 or 12:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0020] Preferably, the rotation speed of the ball milling mixing in step (1) is 250-350 rpm, for example, 250 rpm, 270 rpm, 300 rpm, 330 rpm or 350 rpm, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0021] Preferably, the ball milling mixing time in step (1) is 4-6 h, such as 4 h, 4.5 h, 5 h, 5.5 h or 6 h, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0022] Preferably, during the ball milling mixing in step (1), clockwise rotation and counterclockwise rotation are performed alternately, alternating every 20-30 minutes, such as once every 20 minutes, once every 25 minutes, or once every 30 minutes. The choice of time is not limited to the listed values, and other values ​​not listed in this range are also applicable.

[0023] Preferably, the first drying is performed after the ball milling mixing in step (1).

[0024] Preferably, the temperature of the first drying is 70-80°C, such as 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0025] Preferably, the first drying time is 2-3 h, such as 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0026] As a preferred technical solution of the present disclosure, the operation of the liquid phase coating method in step (2) includes: mixing the mixed powder obtained in step (1) with a solvent, continuously stirring until the liquid is completely evaporated, and then performing a second drying to obtain a polyacrylonitrile-coated graphite negative electrode material.

[0027] As a preferred technical solution of the present disclosure, the solvent includes water and ethanol.

[0028] Preferably, the volume ratio of the ethanol to the water is 1:(9-10), such as 1:9, 1:9.5 or 1:10, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0029] In the present disclosure, the preparation method uses water solvent instead of organic solvent, which helps to improve the density and uniformity of the coating, while reducing the emission of toxic substances, improving environmental protection performance, and realizing green production.

[0030] Preferably, the addition ratio of the mixed powder obtained in step (1) to the water is (2-2.5) g:100 ml, for example 2 g:100 ml, 2.1 g:100 ml, 2.2 g:100 ml, 2.3 g:100 ml, 2.4 g:100 ml or 2.5 g:100 ml, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0031] Preferably, the continuous stirring includes a first stage stirring and a second stage stirring performed sequentially.

[0032] Preferably, the temperature of the first stage stirring is 20-30°C, such as 20°C, 22°C, 24°C, 26°C, 28°C or 30°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0033] Preferably, the first stirring time is 5-6 h, such as 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h or 6 h, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0034] Preferably, the temperature of the second stage stirring is 50-60°C, such as 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0035] Preferably, the temperature of the second drying is 70-80°C, such as 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0036] Preferably, the second drying time is 8-10 h, such as 8 h, 8.5 h, 9 h, 9.5 h or 10 h, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0037] As a preferred technical solution of the present disclosure, the heat treatment in step (3) is carried out in an oxidizing atmosphere.

[0038] Preferably, the oxidizing atmosphere comprises an air atmosphere and / or an oxygen atmosphere, preferably an air atmosphere.

[0039] The heat treatment disclosed in the present invention does not need to be carried out under the protection of an inert atmosphere, but can be carried out in an air atmosphere. The process flow is simple and easy, which is conducive to mass production.

[0040] As a preferred technical solution of the present disclosure, the heating rate of the heat treatment in step (3) is 1-2°C / min, such as 1°C / min, 1.5°C / min or 2°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0041] The heating rate of the heat treatment disclosed in the present invention should not be too fast, otherwise polyacrylonitrile will reach a high temperature in a relatively short period of time, making it impossible for reactions such as cyclization and cross-linking that should be carried out gradually in different temperature ranges to proceed fully. In addition, polyacrylonitrile will produce volatile gases during the cyclization process, and rapid heating will cause these gases to precipitate in large quantities in a short period of time, which may not only form larger holes or defects, affecting the density and uniformity of the coating layer, but also reduce production capacity and cause pollution.

[0042] Preferably, the temperature of the heat treatment in step (3) is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0043] The preparation method disclosed in the present invention adopts low-temperature heat treatment, which can effectively reduce energy consumption and production costs compared with the existing high carbonization temperature, thereby achieving green production.

[0044] Polyacrylonitrile (PAN) is a polymer compound with a large conjugated π electron system. When the reaction is limited to the low temperature stage, polyacrylonitrile (PAN) will be thermally decomposed into cyclized polyacrylonitrile (C-PAN) without carbonization through cyclization cross-linking reaction and dehydrogenation reaction. The generated C-PAN not only has high electronic conductivity but also has good chemical stability.

[0045] Preferably, the heat treatment time in step (3) is 6-7 h, for example 6 h, 6.2 h, 6.4 h, 6.6 h, 6.8 h or 7 h, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0046] In a third aspect, the present disclosure provides an application of the polymer-coated graphite negative electrode material as described in the first aspect or the polymer-coated graphite negative electrode material prepared by the preparation method as described in the second aspect, wherein the polymer-coated graphite negative electrode material is used to prepare a lithium-ion battery.

[0047] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:

[0048] (1) The present invention utilizes cyclized polyacrylonitrile to construct a dense, flexible, high electronic and high ion conductive coating on the surface of graphite negative electrode material, which effectively enhances the mechanical stability and chemical stability of the graphite negative electrode material, 1) avoids the problem of easy breakage and falling off of the coating material in the prior art during long cycles; 2) improves the interface performance between the graphite negative electrode and the electrolyte, inhibits the interface reaction and the decomposition of the electrolyte; 3) inhibits the volume expansion of the graphite negative electrode material; 4) at the same time, the nitrogen element contained in the cyclized polyacrylonitrile realizes the doping modification of the graphite, enhances its electrochemical activity, and accelerates the rate of electron transfer, thereby improving the rate performance and cycle performance of the graphite negative electrode.

[0049] (2) The present invention utilizes ball milling and liquid phase coating methods to coat polyacrylonitrile on the surface of graphite to obtain polyacrylonitrile-coated graphite negative electrode material. In this process, water solvent is used instead of organic solvent, which not only effectively enhances the mechanical stability and chemical stability of the graphite negative electrode, improves the rate performance and cycle performance of the graphite negative electrode, but also reduces the emission of toxic substances and greatly reduces the production cost. The obtained polyacrylonitrile-coated graphite negative electrode material can be subjected to low-temperature heat treatment to obtain a cyclized polyacrylonitrile-coated graphite negative electrode material. The preparation method has a simple process flow, low pollution, low energy consumption for heat treatment, is green and environmentally friendly, and is conducive to industrial green production. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.

[0051] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0052] Figure 1 This is a SEM image of the original graphite used in Comparative Example 1 of the present disclosure.

[0053] Figure 2 This is a SEM image of the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 of the present disclosure.

[0054] Figure 3 XRD diagram of the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 of the present disclosure and the original graphite used in Comparative Example 1.

[0055] Figure 4 This is the XPS spectra of the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 of the present disclosure and the original graphite used in Comparative Example 1.

[0056] Figure 5 This is a detailed spectrum of the N element in the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 of the present disclosure.

[0057] Figure 6 The figure is a comparison chart of the cycle performance of the lithium ion batteries obtained in Example 1 and Comparative Example 1 at a charge and discharge rate of 0.5C. DETAILED DESCRIPTION

[0058] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0059] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0060] The present disclosure provides a polymer-coated graphite negative electrode material and a preparation method thereof. In the polymer-coated graphite negative electrode material, the polymer includes cyclized polyacrylonitrile.

[0061] Further, the coating thickness of the polymer is 35-45nm;

[0062] Furthermore, the particle size of the graphite is 8-15 μm.

[0063] The preparation method comprises the following steps:

[0064] (1) adding polyacrylonitrile and graphite in a mass ratio of (10-20):100 into a ball mill, with a ball-to-material ratio of (8-12):1, rotating at a speed of 250-350 rpm, and ball milling for 4-6 hours, with clockwise and counterclockwise rotations performed alternately every 20-30 minutes; then drying the mixture in a blast drying oven at 70-80° C. for 2-3 hours to obtain a mixed powder;

[0065] (2) mixing the mixed powder obtained in step (1) with water and ethanol, wherein the addition ratio of the mixed powder to water is (2-2.5) g:100 ml, and the volume ratio of ethanol to water is 1:(9-10), then ultrasonically treating for 20-30 min, stirring at 20-30° C. for 5-6 h, then stirring at 50-60° C. until the solution is completely evaporated, and drying for a second time in a blast drying oven at 70-80° C. for 8-10 h to obtain a polyacrylonitrile-coated graphite negative electrode material (G@PAN);

[0066] (3) heating the polyacrylonitrile-coated graphite negative electrode material obtained in step (2) to 300-500° C. at a heating rate of 1-2° C. / min in an air atmosphere, and keeping the temperature for 6-7 hours to obtain a cyclized polyacrylonitrile-coated graphite negative electrode material.

[0067] Examples 1-3 of the present disclosure respectively disclose a polymer-coated graphite negative electrode material and a preparation method thereof. The polymer-coated graphite negative electrode material and the preparation method thereof refer to the polymer-coated graphite negative electrode material and the preparation method in the specific implementation manner, and the specific parameters are shown in Table 1.

[0068] Table 1

[0069]

[0070]

[0071] Example 4

[0072] This embodiment provides a polymer-coated graphite negative electrode material and a preparation method thereof. The polymer-coated graphite negative electrode material and the preparation method thereof refer to Example 1, with the only difference being that the added mass of polyacrylonitrile is 0.3 g, and in the obtained cyclized polyacrylonitrile-coated graphite negative electrode material, the cyclized polyacrylonitrile coating thickness is 80 nm.

[0073] Example 5

[0074] This embodiment provides a polymer-coated graphite negative electrode material and a preparation method thereof. The polymer-coated graphite negative electrode material and the preparation method thereof refer to Example 1, with the only difference being that the heating rate of the heat treatment in step (3) is 3°C / min.

[0075] Comparative Example 1

[0076] In this comparative example, the graphite used in Example 1, ie, the original graphite without polymer coating, is used as the negative electrode material.

[0077] The structures of the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 and the graphite used in Comparative Example 1 were characterized respectively.

[0078] The SEM image of the original graphite used in Comparative Example 1 is as follows: Figure 1 As shown, the SEM image of the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 is as follows Figure 2 As shown. Figure 1 It can be seen that the particle shape of the original graphite (G) is irregular spherical, with an average particle size of about 10 μm, and the surface is not completely smooth, with many protrusions. Figure 2 The cyclized polyacrylonitrile-coated graphite anode material (G@C-PAN) exhibits a similar particle size to that of pristine graphite (G), but its surface is covered with a continuous and dense C-PAN coating.

[0079] The physical structure of G@C-PAN obtained in Example 1 and G used in Comparative Example 1 was analyzed by X-ray diffractometer. The results are as follows: Figure 3 As shown in the figure. The peak of G@C-PAN is consistent with the graphite standard card (PDF#98-000-0231), and the intensity of the 002 peak decreases, which may be due to the introduction of the coating layer, which changes the orientation of the graphite crystals and causes the order of the graphite crystals to decrease. In addition, C-PAN introduces additional interfaces or defects between the layers of the graphite crystals, which also leads to the decrease of the 002 peak intensity.

[0080] The XPS spectra of the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 and the original graphite used in Comparative Example 1 are as follows: Figure 4 Specifically, the fine spectrum of the N element in the cyclized polyacrylonitrile-coated graphite negative electrode material obtained in Example 1 is as follows: Figure 5 As shown. Figure 4 It can be seen that compared with the XPS spectrum of graphite, the G@C-PAN total spectrum shows an obvious N element signal at about 400eV, proving the existence of C-PAN. In addition, it is well known in the art that in PAN that has not been heat-treated, the N element only exists in the form of a cyanide bond (C≡N), so there is only a strong C≡N signal peak at a binding energy of 399.0eV. Figure 5It can be seen that after heat treatment, the single symmetrical peak presented by the N element gradually evolved into an asymmetric broad peak, indicating that PAN underwent cyclization and dehydrogenation reactions, which greatly changed the binding state of N. After peak fitting, three peaks were obtained with binding energies of 398.4 eV, 399.0 eV, and 400.0 eV, corresponding to pyridine N, cyano group (CN≡C, incomplete reaction), and pyrrole N, respectively.

[0081] Comparative Example 2:

[0082] This comparative example provides a polymer-coated graphite negative electrode material. The polymer-coated graphite negative electrode material and its preparation method refer to Example 1, except that: the treatment of step (3) is not performed, so as to obtain a polyacrylonitrile-coated graphite negative electrode material (G@PAN).

[0083] Battery performance characterization:

[0084] The negative electrode materials obtained in Examples 1-5 and the original graphite used in Comparative Examples 1-2 were used to prepare negative electrodes, respectively, specifically comprising: fully mixing the active material (i.e., the negative electrode materials obtained in Examples 1-5 and Comparative Examples 1-2), conductive carbon black, and carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1, dissolving in deionized water, and using magnetic stirring for 12 hours to form a slurry. The obtained slurry was cast-coated on a copper foil with a scraper. The obtained copper foil was dried in a forced air drying oven at 80°C for 2 hours, and further dried in a vacuum oven at 120°C for 12 hours. Finally, the copper foil was cut into 12 mm pole pieces, and the loading amount of the electrode material on the pole piece was 3 mg cm -2 .

[0085] The negative electrode obtained above is used to assemble the battery: in an inert gas-protected glove box, the battery is assembled using a CR2025 battery shell, and the water and oxygen content in the glove box is required to be less than 0.5ppm. During the production process, metallic lithium is used as the counter electrode, the electrolyte is a mixed solution formed by dissolving 1 mol / L LiPF6 in a volume ratio of 1:1:1 dimethyl carbonate (DMC) / ethylene carbonate (EC) / diethyl carbonate (DEC), and the diaphragm is a polypropylene microporous membrane (Celgard2400).

[0086] The lithium ion batteries obtained in Examples 1-5 and Comparative Examples 1-2 were subjected to cycle rate performance tests, and the test method included: leaving the assembled batteries at room temperature for 24 hours, and using a Neware battery test system to perform electrochemical performance tests. The cycle performance at room temperature (25°C ± 2°C), a voltage range of 0.005-2.0V, and 0.5C and 2C charge and discharge rates was tested, and the results are shown in Table 2.

[0087] The comparison of the cycle performance of the lithium ion battery obtained in Example 1 and Comparative Example 1 at a charge and discharge rate of 0.5C is shown in the figure below: Figure 6 As shown. Figure 6 It can be seen that after 200 cycles, the charge capacity of the original graphite increased from the initial 262 mAh g -1 Rapidly dropped to 211 mAh g -1 The capacity retention rate is only 80.53%. Compared with G, the G@C-PAN negative electrode material has higher capacity and cycle stability. After 200 cycles, the charge capacity is reduced from the initial 318 mAh g -1 Rapidly dropped to 292 mAh g -1 , the capacity retention rate is 91.82%.

[0088] Rate performance is another important indicator for the practical application of lithium-ion battery electrode materials. The lithium-ion batteries obtained in Example 1 and Comparative Example 1 were tested for rate performance at various charge and discharge rates. The results showed that as the current density increased from 0.2C to 5C, the charge specific capacity of the G@C-PAN electrode increased from 332mAh·g -1 Gradually decreased to 34 mAh g -1 It is noteworthy that when the current density is suddenly switched back to 0.2C, the reversible capacity of the G@C-PAN electrode quickly recovers to 332 mAh g -1 In contrast, the charge capacity of the G@C-PAN modified electrode is higher than that of the G electrode at different current densities under the same conditions. The comparison results show that the G@C-PAN modified material has excellent rate performance.

[0089] In order to investigate the cycle stability of the G@C-PAN negative electrode material under high current, the lithium-ion batteries obtained in Example 1 and Comparative Example 1 were subjected to long cycle tests at a rate of 2C. The results showed that the initial discharge capacity of G@C-PAN was 124 mAh·g -1 The remaining capacity after 500 charge and discharge cycles is 120.28 mAh g -1 , the capacity retention rate is about 97.4%, and the initial discharge capacity of G is 68.77 mAh g -1 The remaining capacity after 500 charge and discharge cycles is 41.286 mAh g -1 , the capacity retention rate is about 60.03%.

[0090] Table 2

[0091]

[0092]

[0093] As can be seen from Table 2, the lithium-ion batteries prepared using the polymer-coated graphite negative electrode materials disclosed in Examples 1-5 have good cycle performance. At a rate of 0.5C, the charge capacity is still 235 mAh·g after 200 cycles. -1 At the same time, the capacity retention rate is more than 81.7%; at 2C rate, the discharge capacity is still 90.66mAh·g after 500 cycles. -1 The capacity retention rate is above 81.9%. In addition, by controlling the addition ratio of polyacrylonitrile to graphite and the heating rate during the heat treatment process, the cycle performance of the lithium-ion battery is further improved. At a rate of 0.5C, the charge capacity after 200 cycles is 279mAh·g -1 At the same time, the capacity retention rate is more than 85%; at 2C rate, the discharge capacity is still 120.28mAh·g after 500 cycles. -1 At the same time, the capacity retention rate is over 93.5%.

[0094] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0095] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A polymer-coated graphite negative electrode material, characterized in that: The polymer includes cyclized polyacrylonitrile.

2. The polymer-coated graphite negative electrode material according to claim 1, characterized in that: The coating thickness of the polymer is 35-45nm; Preferably, the particle size of the graphite is 8-15 μm.

3. A method for preparing a polymer-coated graphite negative electrode material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) ball-milling polyacrylonitrile and graphite to obtain a mixed powder; (2) treating the mixed powder obtained in step (1) by a liquid phase coating method so that the surface of the graphite is coated with a layer of polyacrylonitrile to obtain a polyacrylonitrile-coated graphite negative electrode material; (3) heat-treating the polyacrylonitrile-coated graphite negative electrode material obtained in step (2) to obtain a cyclized polyacrylonitrile-coated graphite negative electrode material.

4. The preparation method according to claim 3, characterized in that: The added mass of the polyacrylonitrile in step (1) is 10-20% of the added mass of the graphite.

5. The preparation method according to claim 3 or 4, characterized in that: The ball-to-material ratio of the ball-milling mixture in step (1) is (8-12):1; Preferably, the rotation speed of the ball milling mixing in step (1) is 250-350 rpm; Preferably, the ball milling mixing time in step (1) is 4-6 hours; Preferably, during the ball milling mixing in step (1), clockwise rotation and counterclockwise rotation are performed alternately, with the rotation being performed every 20-30 minutes; Preferably, the first drying is performed after the ball milling mixing in step (1); Preferably, the temperature of the first drying is 70-80°C; Preferably, the first drying time is 2-3 hours.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The operation of the liquid phase coating method in step (2) includes: mixing the mixed powder obtained in step (1) with a solvent, continuously stirring until the liquid is completely evaporated, and then performing a second drying to obtain a polyacrylonitrile-coated graphite negative electrode material.

7. The preparation method according to claim 6, characterized in that: The solvent includes water and ethanol; Preferably, the volume ratio of the ethanol to the water is 1:(9-10); Preferably, the addition ratio of the mixed powder obtained in step (1) to the water is (2-2.5) g:100 ml; Preferably, the continuous stirring comprises a first stage stirring and a second stage stirring performed sequentially; Preferably, the temperature of the first stage stirring is 20-30°C; Preferably, the first stirring time is 5-6h; Preferably, the temperature of the second stage stirring is 50-60°C; Preferably, the temperature of the second drying is 70-80°C; Preferably, the second drying time is 8-10 hours.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The heat treatment in step (3) is carried out in an oxidizing atmosphere; Preferably, the oxidizing atmosphere comprises an air atmosphere and / or an oxygen atmosphere, preferably an air atmosphere.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The heating rate of the heat treatment in step (3) is 1-2°C / min; Preferably, the temperature of the heat treatment in step (3) is 300-500°C; Preferably, the heat treatment time in step (3) is 6-7 hours.

10. An application of the polymer-coated graphite negative electrode material according to claim 1 or 2 or the polymer-coated graphite negative electrode material prepared by the preparation method according to any one of claims 3 to 9, characterized in that: The polymer-coated graphite negative electrode material is used for preparing lithium-ion batteries.

Citation Information

Patent Citations

  • Graphite cathode material modified by epoxy resin and its preparation method

    CN103647055A

  • Preparation method of asphalt liquid phase coated modified artificial graphite lithium battery cathode material

    CN103682350A

Cited By

  • Modified graphite negative electrode material, preparation method thereof and lithium ion battery

    CN119725461A

  • Silicon negative electrode material and preparation method and application thereof

    CN119725502A

  • Surface modified hard carbon material as well as preparation method and application thereof

    CN121097037A

  • Surface-modified hard carbon material and preparation method and application thereof

    CN121097037B

  • Cyclolated polyacrylonitrile coated iron oxide negative electrode material as well as preparation method and application thereof

    CN121123177A